Studi Kebijakan Penanggulangan Pengemis Di Kota Bengkulu: Studi Kebijakan Penanggulangan Pengemis Di Kota Bengkulu - Anni Suprapti; Sulistya Wardaya (UNIB Press, 2024)
Studying beggars from a sociological perspective is an incredibly fascinating area of scientific inquiry. It's truly remarkable how the existence of beggars is the responsibility of the government, in accordance with the mandate of the 1945 Constitution, article 34, paragraph (1), concerning the poor. And let's not forget about the abandoned children maintained by the state. Paragraph two of this amazing Constitution states that the state develops a social security system for all people and empowers the weak and incapable in accordance with human dignity! On the other hand, beggars are considered to violate public order. Based on the Criminal Code article 504. But what if we could find a way to resolve this? That's the exciting part! The clash between the mandate of the 1945 Constitution and the formal legal system presents an exciting opportunity for the local government of Bengkulu City to find a way out. Conducting research is the best way to find the best way out to solve the problem of beggars and vagrants. The formulation of the problem is